Enhancing the Infrared Photoresponse of Silicon by Controlling the Fermi Level Location within an Impurity Band. (21st February 2014) - Simmons, Christie B.; Akey, Austin J.; Mailoa, Jonathan P.; Recht, Daniel; Aziz, Michael J.; Buonassisi, Tonio
<x xml:space="preserve">Abstract</x> Strong absorption of sub‐band gap radiation by an impurity band has recently been demonstrated in silicon supersaturated with chalcogen impurities. However, despite the enhanced absorption in this material, the transformation of infrared radiation into an electrical signal via extrinsic photoconductivity—the critical performance requirement for many optoelectronic applications—has only been reported at low temperature because thermal impurity ionization overwhelms photoionization at room temperature. Here, dopant compensation is used to manipulate the optical and electronic properties and thereby improve the room‐temperature infrared photoresponse. Silicon co‐doped with boron and sulfur is fabricated using ion implantation and nanosecond pulsed laser melting to achieve supersaturated sulfur concentrations and a matched boron distribution. The location of the Fermi level within the sulfur‐induced impurity band is controlled by tuning the acceptor‐to‐donor ratio, and through this dopant compensation, three orders of magnitude improvement in infrared detection at 1550 nm is demonstrated.